Analysis of the Content of the Auditor's Reports on a Sample of Public Interest Entities in Poland - Monika TUREK – RADWAN; Anna MAZURCZAK - MĄKA (Communications of International Proceedings, 2021)
The financial auditing system in Poland has undergone significant changes in recent years, which largely result from the need to implement solutions provided for in European Directives. The article analyzes the functions of statutory audits. The main objective of this study is the analysis of statutory auditor opinions and reports disclosed by companies listed on the Warsaw Stock Exchange and the determination of the relevant information contained in the opinions and reports disclosed by the listed companies.  Thus defined, the main objective allows for the identification of specific goals, which include: characterization of the types of opinions issued by auditors examining the financial statements of listed companies in the years 2005-2020, identification of reasons for the issuance of qualified opinions in the analyzed sample, identification of those reports in which the auditor gives quantitative results of the threat to going concern (e.g. Altman’s or Hołda’s method), In order to achieve the main objective and the specific goals, opinions and reports of expert auditors for 25 of listed companies in the years 2005-2020 had been analyzed. The results obtained suggest that the majority of opinions are unqualified opinions (which in some cases contain additional explanations).
Keywords: Statutory audit; auditor’s opinion; Warsaw Stock Exchange